Outcome of Non-Invasive Ventilation for Acute Exacerbation of Chronic Obstructive Pulmonary Disease in Tertiary Level Hospital - Devkota, Kriti; Pradhan, Anima (Journal of National Heart and Lung Society Nepal, 2026)
Background: Acute exacerbation of Chronic Obstructive Pulmonary Disease (AECOPD) complicated by acute hypercapnic respiratory failure frequently requires Intensive Care Unit (ICU) admission and is associated with significant mortality and morbidity. Non-Invasive Ventilation (NIV) is an established modality of treatment that reduces the need of mechanical ventilation and improves outcomes. This study aimed to evaluate the effectiveness of NIV use for AECOPD in a tertiary-level hospital in Nepal. Methods: This observational study was conducted in the Department of Anesthesia and Critical Care in the College of Medical Sciences, Bharatpur, Chitwan, from June 2025 to May 2026. A total of 260 patients with AECOPD with Type II respiratory failure were included. Baseline demographic and clinical data were recorded. Arterial blood gas (ABG) was done before initiation of NIV and 4 hours after. NIV success, need for invasive ventilation, and clinical outcomes were analyzed. Results: Out of 260 patients, 161(61.9%) were males, and 99 (38.1%) were females. The mean age of patients was 67.49 ± 12.49 years. NIV use improved ABG parameters significantly within 4 hours of use, with mean pH increasing from 7.24 ± 0.06 to 7.30 ± 0.07 and mean PaCO2 decreasing from 88.54 ± 14.31 mmHg to 75.68 ± 13.43 mmHg. NIV was successful in 229 (88.1%) patients, while 31(11.9%) required escalation of care. The mean duration of NIV use was 30.69 ± 5.38 hours. Conclusion: NIV is an effective supportive modality in AECOPD with type II respiratory failure, resulting in a higher rate of successful treatment.